The New Body of the “Thaw” in Vasily Aksyonov’s Novella "Colleagues" and its Film Adaptation - Nyagolova, Natalia (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article focuses on the concept of body representation in Vasily Aksyonov’s short novel Colleagues and in Aleksei Sakharov’s 1962 film of the same title. The new ways in which the body began to be represented during the “Thaw” are reported – its medicalization, eroticization, and electronization. The paper describes the three models of corporality from the novella and traces their transformations in the screen adaptation.